Impacts of Photooxidation on Commercially Available Homo and Copolymers of Polypropylene on Their Microstructure and Mechanics: A Cross‐Sectional Analysis - Marta Chiapasco; Michele Valsecchi; Gavin Hill; Christopher Wallis; Alexandra E. Porter; Finn Giuliani (Nano Select)
ABSTRACT Polyolefin degradation is widely studied to assess the lifetime of packaging materials. In this work, a combination of bulk (DSC, GPC, 13C‐NMR, XRD), surface (FTIR) and cross‐sectional characterization (Raman spectroscopy and nanoindentation) was used to examine changes in the mechanical properties and microstructure of two different commercially‐available polyolefins, with similar crystallinities, produced by injection molding—a polypropylene homopolymer (PPH) and a polypropylene random copolymer (PPRC)—aged under accelerated UV‐A conditions. The aim was to characterize the variations in the crystallinity and microstructure across the cross‐section of these materials. Our results suggest that the presence of ethylene comonomer units in PPRC results, on average, in smaller crystal dimensions, leads to improved packing, and a more homogeneous microstructure and hardness across the cross‐section of the sample. The ethylene monomers stabilize PPRC from oxidation during the first 14 days of accelerated aging, but eventually the rate of degradation matches the PPH at 28 days of aging, probably because of the higher surface area to volume ratio of the smaller crystals. The work emphasizes the importance of incorporating ethylene comonomers into polyolefins to limit variation of the microstructure across the core to the skin layer, for improved future design of packaging that degrades fully.